Mouse Lambda-Chain Sequences - Cesari, Italo M. (1973)
Amino-acid sequences of the variable regions of three lambda chains produced by plasmacytomas of BALB/c mice are compared. Two are almost certainly identical and one differs from these by three amino acids. These findings extend our earlier conclusion on the relative uniformity of sequences in this type of immunoglobulin light chain. With amino-acid sequence data on two additional lambda chains, eight mouse lambda chains studied to date are indistinguishable and four probably differ from these by one, two, or three amino acids.